Analisis Penginapan Berkonsep Syariah Studi Implementasi Reddoorz Syariah Jalan Ahmad Yani Kota Jambi - Pratiwi, Heni; Hutabarat, Zuhri Saputra (Jurnal Ekonomi Bisnis Digital, 2023)
This research aims to determine the implementation model of Reddoorz Jalan Ahmad Yani Telanai, Jambi City, as well as identifying the obstacles faced in the implementation process. This research uses qualitative methods, with a field research approach, namely mapping the potential and existing conditions of the Reddoorz Hotel/lodging on Jalan Ahmad Yani, then looking for connections with the phenomenon and concept of sharia lodging. The data collection methods used are divided into three: First, observation in the form of direct observation regarding the existing condition of the Reddoorz Inn on Jalan Ahmad Yani as a halal accommodation. Second, interview the person in charge or the innkeeper. Third, documentation studies sourced from articles and references relevant to the research topic. The data analysis technique uses an inductive approach to help interpret the various data obtained. The results of this research show that there are 5 indicators of halal lodging that have been implemented by Reddoorz Jalan Ahmad Yani Telanai, such as (1) Services that adopt Islamic principles. (2) Lodging service providers have discipline and understanding of Islamic teachings. (3) Tourist activities and activities do not conflict with Islamic principles. (4) Availability of a halal kitchen. (5) Availability of Muslim facilities for praying.